(untitled) (Journal of the College of Basic Education, 2026)
This paper contributes to the ongoing generalization of quasi-normal operators by introducing a new class termed the -Fuzzy Soft Quasi-Normal operator, abbreviated as -FSQN operator. The primary objectives are to define this operator, examine its fundamental properties, and establish its basic operations. The conceptual framework is supported by pertinent examples. Finally, the relationships between the -FSQN operator and other known types of fuzzy soft operators are explored.